Previews and premises: An Interview With Alvin Toffler - Toffler, Alvin (London, Pan Books, 1984)
A highly personal look at jobs, identity, sex roles, information age politics, hidden forces driving the economy, and the pitfalls and promises of social change.
Keywords: "Toffler, Alvin"